Incidental radiological finding of a renal tumour leading to the diagnosis of birt-hogg-dube syndrome - M Schreuer (Journal of the Belgian Society of Radiology, 2011)
Birt-Hogg-Dubé (BHD) syndrome is a rare autosomal dominant condition characterised by benign tumours of the hair follicle, renal cancer, pulmonary cysts and spontaneous pneumothorax. We report the diagnosis of a BHD syndrome achieved after incidental radiological finding of a renal tumour in a 24-year old man. The patient also displayed recurrent pneumothoraces and showed to have cysts in the basis of both lungs. The association of recurrent pneumo - thoraces and renal neoplastic disease should alert for the possible presence of this syndrome.